Implementasi Kebijakan Pasar Tradisional (Studi Kasus : Renovasi Pasar Desa Pakis Baru Kecamatan Nawangan Kabupaten Pacitan) - Ovyan Subekti; Syaiful Mahfud Abdulloh; Dian Suluh Kusuma dewi (Fakultas Ilmu Sosial dan Ilmu Politik, 2019)
This study attempts to know of policy the village administration concerning the arrangement traditional markets and obstacles in implementation of policy. Design research used in this research is research descriptive qualitative. A subject in this study is the village head Pakis Baru, and traders and the village around new market. Data collection was carried out by means of observation, interview, and documentation. Data analysis model according to use interaction milles huberman reduction, and the data presentation of data, and withdrawals conclusion. Technique using a technique of the validity of data triangulation. The research results show that the implementation of the management of the policy traditional markets do not to walk to work optimally, this can be seen from : 1). The absence of village regulations as a guideline in manages the markets , as well as ignorance and the organizer of market management activities do not participate renovation village. 2). Not unification sources is required from producers to consumers. 3). Complex causality happened relations, 4). The implementation of a policy which is not in accordance with the initial concept, 5). The absence of understanding to the purpose, communication, coordination, the deployment of the duties of correctly, 6). The misuse of authority the market like a parking lot.